2005
DOI: 10.1373/clinchem.2004.039636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Monoclonal Antibodies for Prostate-Specific Antigen (PSA) with Potency to Recognize PSA Bound to α2-Macroglobulin

Abstract: Background: Different molecular forms of prostatespecific antigen (PSA) have been used to differentiate between benign prostatic hyperplasia and prostate cancer. Detecting PSA bound to endogenous inhibitors such as ␣ 1 -antichymotrypsin (ACT) and ␣ 2 -macroglobulin (␣ 2 M) is often difficult because of epitope masking or sensitivity problems. Here we report the characterization of four novel mouse monoclonal antibodies (mabs) obtained by immunization with PSA-␣ 2 M complexes. Their ability to detect free PSA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Plasmid pCMV-GLUC was obtained from Prolume Nanolight, Inc.; the TCF Reporter Plasmid kit was from Millipore; TransIT-LT1 was from Mirus Corporation; and the Gaussia luciferase transfection kit and coelenterazine were from PJK. A2M (clone α1-IIE7) and prostate-specific antigen (PSA; clone 1B7) mAbs were used as described previously (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pCMV-GLUC was obtained from Prolume Nanolight, Inc.; the TCF Reporter Plasmid kit was from Millipore; TransIT-LT1 was from Mirus Corporation; and the Gaussia luciferase transfection kit and coelenterazine were from PJK. A2M (clone α1-IIE7) and prostate-specific antigen (PSA; clone 1B7) mAbs were used as described previously (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the epitope recognized by antibody 5E4 is accessible at least in some of the A2M complexes although this complex is not detected by sandwich immunoassays [33]. Some PSA antibodies have been shown to also react with PSA bound to human A2M [39]. When a protease reacts with human A2M, the bait region is cleaved, A2M engulfs the protease, and activation of thiol ester groups in A2M leads to formation of covalent bond between the two proteins [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…27 Notably, the design of these studies was not based on the subsequently reported investigations showing that PSA in the extracellular fluids occurs in many different molecular forms with distinctly different rates and mechanisms of clearance. 17,20,28,29 Also, the antibodies used in prior studies to detect PSA in vivo were polyclonal; hence, they could cross-react with other antigens and did not discriminate fPSA from cPSA. This feat was not possible until the early 1990s when it was first reported on the discovery of fPSA and the development of monoclonal antibodies specific to antigenic epitopes uniquely accessible on fPSA alone, but unable to detect PSA linked to protease inhibitors, such as ACT.…”
mentioning
confidence: 99%